1996
DOI: 10.1002/ana.410400413
|View full text |Cite
|
Sign up to set email alerts
|

Speech‐induced changes in corticospinal excitability

Abstract: The aim of the experiments was to investigate the effects of speech on the excitability of corticospinal pathways to human hand muscles. Single transcranial magnetic stimuli were given randomly over the hand area of either the left or right motor cortex of 10 right-handed and 3 left-handed normal volunteers. Electromyographic responses were recorded in the relaxed first dorsal interosseous muscle while the subjects (a) read aloud a piece of text, (b) read silently, (c) spoke spontaneously, or (d) made sounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 12 publications
7
99
1
1
Order By: Relevance
“…We counterbalanced the up-or down-position of the verbal descriptors in order to avoid participants to plan their response in advance. A verbal, rather than a motor, response was required at the end of each video clip to avoid MEPs contamination (Tokimura et al 1996;Meister et al 2003;Gentilucci et al 2006). Twenty-four repetitions for each of the 3 possible actions with the light or the heavy object were presented, thus leading to a total of 144 trials.…”
Section: Methodsmentioning
confidence: 99%
“…We counterbalanced the up-or down-position of the verbal descriptors in order to avoid participants to plan their response in advance. A verbal, rather than a motor, response was required at the end of each video clip to avoid MEPs contamination (Tokimura et al 1996;Meister et al 2003;Gentilucci et al 2006). Twenty-four repetitions for each of the 3 possible actions with the light or the heavy object were presented, thus leading to a total of 144 trials.…”
Section: Methodsmentioning
confidence: 99%
“…4,7,17) However, rTMS appears to be less reliable than the Wada test. 6) Lateralized speech effects on the excitability of the cortical hand motor area were first demonstrated in 1996, 28) and has been replicated and confirmed in several studies. 15,16,25) The effect is restricted to the hand area because MEPs from the leg area are unchanged by the task.…”
Section: Discussionmentioning
confidence: 87%
“…Because the Wada test is invasive, other methods have been proposed, such as positron emission tomography, 20) fMR imaging, 3) functional Doppler sonography, 14) assessment of event-related brain potentials, 9) and TMS. 19,28) TMS is a noninvasive method to investigate the awake human nervous system. 2) Speech suppression and speech activation studies have been reported in human subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12) We previously showed that single magnetic stimuli delivered at intensities safe for use with normal subjects could be used to detect lateralized effects on brain function. 23) Electromyographic (EMG) responses in the relaxed hand muscles evoked by transcranial stimulation of the motor cortex of the dominant hemisphere were enhanced if stimuli were delivered while subjects read aloud. This effect clearly depended on lateral dominance in normal subjects.…”
Section: Introductionmentioning
confidence: 99%